Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.4236/oalib.1105715
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Pediatric Medical Emergencies at the Kindu Reference General Hospital (HGRK): State of Affairs and Perspectives

Abstract: The management of pediatric medical emergencies is a focus of WHO's strategy to reduce child and adolescent morbidity and mortality worldwide. It requires the synergy of several inputs including infrastructure, equipment and a sufficiently trained staff. The aim of our study was to present the epidemiological aspects of pediatric medical emergencies at Kindu General Reference Hospital in order to facilitate the projection of the actions to be carried out. To do this, we undertook a cross-sectional, descriptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…Infectious diseases were responsible for over 75% of mortality in the present study. This finding corroborates studies in some regions of Nigeria 7,10,14,16,19) , and the Democratic Republic of Congo 20) , and reports by the World Health Organization stating infectious diseases as the leading cause of childhood mortality 1,21) . Contrary to the above studies, Jofiro et al 6) in Ethiopia reported cardiovascular and infectious diseases as the most and the third common cause of death, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Infectious diseases were responsible for over 75% of mortality in the present study. This finding corroborates studies in some regions of Nigeria 7,10,14,16,19) , and the Democratic Republic of Congo 20) , and reports by the World Health Organization stating infectious diseases as the leading cause of childhood mortality 1,21) . Contrary to the above studies, Jofiro et al 6) in Ethiopia reported cardiovascular and infectious diseases as the most and the third common cause of death, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…The average duration of hospitalization is 4 days. In the Democratic Republic of the Congo, 50% is the rate recorded for the length of hospitalization of children with an emergency sign of fewer than 4 days [ 7 ]. In France, 72% of patients stayed more than 4 days in the emergency department [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…By definition, pediatric emergencies are all morbid conditions that threaten a child´s life in a more or less short period and require rapid and adequate care [ 6 ]. This definition is not always respected because of the pediatric emergency department (PED) heterogeneity and the different perceptions of healthcare by staff and parents [ 5 , 7 ]. As a result, the PED suffers from overcrowding, which has become a universal and growing problem.…”
Section: Introductionmentioning
confidence: 99%
“…The hospital prevalence of pediatric life-threatening emergencies was 42.4%. Nzame et al, in Gabon (2020),Guedenon et al in Togo (2017) andKingwengwe et al in DRC (2019), had reported a prevalence of PLTE which varied from 18.3% to 21.4% in their respective previous studies[7] [8][9]. The high trend in our series could be explained by the geographical location of this referral hospital which has a technical platform to receive patients with serious pathologies on the one hand and on the other hand, access to care is facilitated through the issuance of internal vouchers (green vouchers) with deferred recovery of care costs.…”
mentioning
confidence: 95%
“…In previous studies in Africa, infectious pathologies were often found in children under 5 years of age consulting at pediatric emergencies, malaria being the most common etiology. Pediatric emergency unit mortality rates ranged from 8% to 17.3% [5] [6] [7]. Few studies have been conducted on critical pediatric emergencies in a resource-limited setting, especially in Cameroon where no studies were available.…”
Section: Introductionmentioning
confidence: 99%